Assessing a b-learning teaching approach and students' learning preferences in higher education - Cardoso, Teresa Margarida Loureiro (2019)
N.B. this is the preprint version of the paper indicated below. T. Cardoso, F. Pestana, J. Pina (2019). Assessing a b-learning teaching approach and students' learning preferences in higher education, EDULEARN19 Proceedings, pp. 10007- 10012. Appears in: EDULEARN19 Proceedings Pages: 10007-10012 Publication year: 2019 ISBN: 978-84-09-12031-4 ISSN: 2340-1117 doi: 10.21125/edulearn.2019.2502 Conference name: 11th International Conference on Education and New Learning Technologies Dates: 1-3 July, 2019 Location: Palma, Spain https://library.iated.org/view/CARDOSO2019ASS https://library.iated.org/publications/EDULEARN19/start/1500